2018
DOI: 10.1007/s00059-017-4675-x
|View full text |Cite
|
Sign up to set email alerts
|

Nine-month clinical outcomes in patients with diabetes treated with polymer-free sirolimus-eluting stents and 6‑month vs. 12‑month dual-antiplatelet therapy (DAPT)

Abstract: PF-SES are safe and effective in daily clinical routine with low rates of TLR and MACE in patients with diabetes and stable disease. Our data suggest that extending the duration of DAPT beyond 6 months does not improve MACE or TLR at 9 months in patients with stable CAD (ClinicalTrials.gov Identifier NCT02629575).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…MI, and all-cause death [31]. Based on these findings, they suggested that short-term DAPT was a reasonable strategy for patients with DM after PCI.…”
Section: Plos Onementioning
confidence: 91%
“…MI, and all-cause death [31]. Based on these findings, they suggested that short-term DAPT was a reasonable strategy for patients with DM after PCI.…”
Section: Plos Onementioning
confidence: 91%
“…To support the results of this analysis, the International ISAR 2000 All Corner Registry also showed no significant difference in the stent thrombosis rate with short- versus long-term DAPT use following PCI [15]. One out of 165 and 340 participants with short- (≤ 6 months) and long-term (> 6 months) DAPT use, respectively, suffered late stent thrombosis.…”
Section: Discussionmentioning
confidence: 65%
“…Of 3506 articles, 652 were excluded after removing duplicates, 2830 were excluded after reviewing the title and abstract, and additional six studies were excluded because they contained unpublished data, were observational trials, or could not be grouped appropriately [24,25,26,27,28,29] (Figure 1). Eighteen trials were ultimately included with a total of 20536 diabetes patients randomly assigned to receive either short-term (≤3 months), midterm (6 months), standard-term (12 months), or extended-term (>12 months) DAPT regimens [10,11,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45].…”
Section: Search Results and Study Characteristicmentioning
confidence: 99%